Analisis Pengaruh Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Handphone Xiaomi dengan Citra Merek sebagai Variabel Intervening di Kota Semarang - Ryan Syafi Amanullah; Yoestini Yoestini (Faculty of Economics and Business Diponegoro University, 2025)
In the era of globalization like today, Handphones provide lifestyle changes that ultimately Handphones become a very important need every day. Active Handphone users experience a large increase every year so that there is tight competition in the Handphone business. Therefore, it causes enthusiasm for business people to innovate their product marketing strategies that allow business people in the technology industry, especially Handphones, to meet consumer desires. One of the companies engaged in technology is Xiaomi, this company needs to innovate quickly with the increasingly rapid development of technology in order to improve the brand image of consumers. But the company needs to observe the factors that strengthen brand image, namely promotion and product quality. By improving these aspects, consumers can become more confident, realizing the brand image of consumers makes the Xiaomi company able to increase consumer purchasing decisions. In addition, there are differences in the results of research on the relationship between promotion and product quality on purchasing decisions in previous studies. Which finally became a phenomenon and the gap became the basis for this study. This study aims to test and prove that promotion and product quality have an effect on consumer purchasing decisions. Data collection from this study involved 120 respondents with the main criteria of Xiaomi Handphone product consumers and domiciled in the city of Semarang. The data obtained were then analyzed using the Structural Equation Model (SEM) with the AMOS program version 24. The conclusion of the study obtained promotion has a negative and insignificant effect on brand image. Furthermore, product quality has a positive and significant effect on brand image. Then the researcher found that promotion has a positive and significant effect on purchasing decisions. Then product quality has a negative and insignificant effect on purchasing decisions. Finally, the researcher found that brand image has a negative and insignificant effect on purchasing decisions.